Racist Fake News in United States' History: Lessons for Public Administration. (3rd September 2019) - Heckler, Nuri; Ronquillo, John C.
Abstract : This article explores the relationship between fake news and administrative racism using post-Reconstruction U.S. history. Administrative racism is when public organizations severely harm people of color. This article argues that fake news based on racist ideas feed a climate where administrative racism becomes more likely. In one decade, from 1877–1887, the Republican Party drifted from its moorings as the party of emancipation, equal protection, and Reconstruction to creating the conditions in which anti-Black violence thrived, Chinese immigrants were legally excluded, and American Indian tribes were dispossessed of 80% of their treaty-promised land. According to historians, fake news spread racist ideas in ways that made each of these policies more likely. The legacies of that racist fake news and those policies impact modern debates on integration, immigration, and equality, with implications for public administration.